Synthesis and Antibacterial Activity of Some Benzothiazole Deriavatives of S-triazine - Desai, Pratibha; Champaner, A.C.; Desai, K.R. (Asian Journal of Chemistry, 2010)
In the present work, authors report the synthesis and antibacterial activity of some benzothiazole derivatives of S-triazine.